Experiences and challenges of nuclear safeguards activities in Bangladesh. (17th December 2022) - Mahmud, Abdullah Al; Soner, Md. Abdul Malek; Hossain, Md. Moazzem; Hossain, Md. Sayed; Usha, Tamanna Yeasmin; Islam, Md. Maidul; Zoardar, A.K.M. Raushan Kabir; Haque, Ashraful; Uddin, Mohammad Mezbah; Jahan, Nusrat
As a Non-Nuclear-Weapon State (NNWS), and party to the Treaty on the Non-Proliferation of Nuclear-Weapons Treaty (NPT), Bangladesh concluded Comprehensive Safeguards Agreement (CSA) and thereafter signed Protocol Additional to Safeguards Agreement (AP) with International Atomic Energy Agency (IAEA) in order to fulfil its non-proliferation commitments. The objectives of International Nuclear Safeguards are to provide assurances to the international community that nuclear materials and nuclear technology are being used for peaceful uses. Bangladesh Atomic Energy Commission's (BAEC) TRIGA Research Reactor (BTRR) has been prime concern of IAEA's safeguards inspection since its establishment. Moreover, with the construction of its first nuclear power plant Rooppur Nuclear Power Plant, Bangladesh intends to strengthen its approach to IAEA safeguards in more advanced level. Thus, the study would be highly beneficial for successful implementation of IAEA safeguards obligations in near future that are associated with the upcoming nuclear power plant and fulfil the state's commitment to nuclear non-proliferation.